Mediating effect of smartphone addiction on the relationship between sociotropy personality trait and loneliness in nursing students - Uzdil, Nurcan; Şimşek, Nuray (Journal of Dependence, 2023)
Objective: The aim of this study was to examine the mediating effect of smartphone addiction on the relationship between sociotropy personality trait and loneliness in nursing students. Method: The study was carried out in descriptive-relational design. The sample of the study consisted of 273 nursing students who met the criteria for inclusion in the research. The data were obtained by the researchers online using the personal information form, Sociotropy-Autonomy Scale, Smartphone Addiction Scale, and De Jong Gierveld Loneliness Scale. Results: SAS-SV mean score was 30.98 ± 10.66, sociotropy mean score was 53.92 ± 16.13, autonomy mean score was 70.47 ± 15.34, and DJGLS mean score was 25.43 ± 6.87. A statistically significant and positive correlation was found between sociotropy and autonomy, SAS-SV and DJGLS. In addition, the mediating role of smartphone addiction was found to be moderate. 14.2% of nursing students’ smartphone addiction scores are explained by sociotropy. 8.2% of DJGLS scores are explained by sociotropy and SAS-SV. Conclusion: Smartphone addiction moderately mediated the relationship between sociotropy personality trait and loneliness among nursing students. At the same time, sociotropy personality trait has a direct predictive effect on loneliness. In addition to the scientific development of students, it can be suggested that activities for the development of sociotropy-autonomy personality traits should be included in nursing education programs.